PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP TINGKAT KEPUASAN MAHASISWA (STUDI KASUS DI UNIVERSITAS AZZAHRA JAKARTA) - Asep Candra Hidayat (Majalah Ilmiah Bijak, 2016)
This study aimed to analyze how much influence service quality, customer value on the level of customer satisfaction. The sampling method used is Proportionate Random Sampling. The sample in this study followed the formula Slovin, or as many as 100 students of  Azzahra University, Jakarta.Data that has met the test of validity and reliability further processed to produce a regression equation Y = 0.484+ 0021 0686 X1 + X2, where Y is the variable rate Student Satisfaction, X1 is a variable Quality of Service and Customer Value X2 is variable.Hypothesis testing using t test showed that each of the independent variables studied was shown to significantly affect partially dependent variable Student Satisfaction.Quality of service partially positive effect on customer satisfaction shown by the r value of 0.663, which means a strong relationship between them. While the value of the coefficient of determination (R2) amounted to 0,439, which means that service quality may explain the variable of student satisfaction of 43.9%, while the remaining 56.1% is explained by other variables.Customer value partially positive effect on customer satisfaction shown by the r value of 0.832 which means the relationship between them is very strong. While the value of the coefficient of determination (R2) amounted to 0,692, which means that service quality may explain the variable of student satisfaction at 69.2%, while the remaining 30.8% is explained by other variables.Then through the F test can be known simultaneously that both variables of service quality and customer value has a significant impact on customer satisfaction shown by the r value of 0.835 which means the relationship between them is very strong. While the value of the coefficient of determination (R2) is equal to 0.697, which means that service quality may explain the variable of student satisfaction at 69.7%, while the remaining 30.3% is explained by other variables.